Cellular and molecular mechanism in neurodegeneration: Possible role of neuroprotectants. (1st March 2021) - Basha, Fathima Hajee; Waseem, Mohammad; Srinivasan, Hemalatha
Abstract : In recent years, neurodegeneration has been recognized as a clinical condition that is characterized by neuronal death, dementia, and gradual diminish of cognitive function, poor body coordination and motor disorders. Several studies deciphering cellular and molecular mechanisms show a promising insight for several kinds of damages including neurodegeneration in central nervous system. In addition, there has been an inflammatory key mechanism involved in neurodegenerative disorders. There is a paucity of literature in both cellular‐ and molecular‐mediated targets in damaged neurons at both in vitro and in vivo research models. It has been notified that CNS has a very restricted magnitude of regeneration. Numerous key factors have also been studied and considered as possible culprit of neurodegeneration. Autophagy is a well‐known degradation process wherein vesicular machinery as autophagosome transports cytoplasmic contents to the lysosomes. In earlier reports, a bridging connection between autophagy and its associated mechanism has been established. Natural compounds as a neuro‐therapeutics have been recognized in neurodegeneration. In our review, we discuss the mechanisms for the onset and progression in neurodegeneration, via inflammation and autophagic machine available in cellular compartments in CNS. This review also discusses about the neuroprotective efficacy of natural compounds against neurodegeneration episodes displays in neuronal platform.